2005
DOI: 10.1016/j.jcrs.2004.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of corneal biomechanical properties on intraocular pressure measurement

Abstract: The simulation based on the model demonstrated quantitatively that variations in each corneal variable cause errors in tonometry IOP readings. The simulation results indicate that differences in corneal biomechanics across individuals may have greater impact on IOP measurement errors than corneal thickness or curvature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
510
3
25

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 706 publications
(558 citation statements)
references
References 44 publications
20
510
3
25
Order By: Relevance
“…Goldmann applanation tonometry (GAT) is considered the gold standard for IOP measurement; 1 its accuracy is, however, influenced by corneal thickness, curvature, and biomechanical properties, such as rigidity, viscosity, elasticity, hydration, [2][3][4][5][6] which have shown to have high interindividual variability and to be affected by corneal pathology and surgery. 3,4,[7][8][9] Studies have shown erroneous postoperative IOP readings with GAT after keratoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Goldmann applanation tonometry (GAT) is considered the gold standard for IOP measurement; 1 its accuracy is, however, influenced by corneal thickness, curvature, and biomechanical properties, such as rigidity, viscosity, elasticity, hydration, [2][3][4][5][6] which have shown to have high interindividual variability and to be affected by corneal pathology and surgery. 3,4,[7][8][9] Studies have shown erroneous postoperative IOP readings with GAT after keratoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Em um modelo matemático, Liu e Roberts (5) , observaram uma maior influência de variações relacionadas com a tensão da superfície relacionadas pela resistência da córnea (módulo de Young), potencialmente determinando maior "erro" na TAG, comparando-se com os efeitos relacionados com a espessura central e com a ceratometria.…”
Section: Discussionunclassified
“…Por outro lado, quanto mais grossa a córnea, maior seria sua resistência e maior a pressão medida, valor hiperestimado por meio da TAG. Além da espessura, outras características como a curvatura da córnea, também são reconhecidamente importantes, de modo que córneas mais planas tendem a apresentar maior resistência para a aplanação e gerar valores mais elevados (4,5) . Entretanto, a medida da pressão intraocular sofre influência da córnea de forma mais complexa.…”
Section: Introductionunclassified
“…These are impacted by adhesion properties and the prism material, which exert a pressure that offsets the effect of corneal resistance. 12 The acrylic Tonosafe tip may affect the adhesion properties of the tear film, leading to measurement errors as well.…”
Section: Introductionmentioning
confidence: 99%